Strategies for expanding childhood vaccination in the Americas following the COVID-19 pandemic - Carla Magda Allan Santos Domingues; Marco Aurelio P. Safadi; Carlos Espinal; Ruby Trejo Varon; Francisco Becerra-Posada; Sebastián Ospina-Henao (Pan American Health Organization, 2024)
Objective. To provide an overview of the status of the childhood vaccination schedule in the Americas, outline program structures, and identify updated implementation strategies to improve vaccination coverage following the COVID-19 pandemic. Methods. A group of experts in pediatrics, epidemiology, vaccines, and global and public health discussed the current status of the childhood vaccination schedule in the Americas, describing the program structure and identifying new implementation strategies that have the potential to improve vaccination coverage in the post-pandemic context, after the challenges COVID-19 presented for more than two years. Results. The Americas currently face a high risk of resurgence of diseases that were previously controlled or eliminated. Therefore, it is important to find new strategies to educate citizens on the risks associated with lower vaccination rates, especially in children. Conclusions. New strategies along with strong mobilization of the population and advocacy by citizens are necessary to prevent antivaccination groups from gaining a stronger presence in the region and jeopardizing the credibility of the Expanded Program on Immunization.